2012
DOI: 10.2147/amep.s31726
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing knowledge in the light of undergraduate clinical pharmacology and therapeutics teaching in India: views of first-year postgraduate students

Abstract: ObjectivesThe study aimed to review the prescribing knowledge of first-year postgraduate doctors in a medical college in India, using the principles of good prescribing, to suggest strategies to improve rational prescribing, and to recommend what curriculum planners can do to accomplish this objective.MethodsFifty first-year postgraduate doctors were asked to fill in a structured questionnaire that sought information regarding their undergraduate training in clinical pharmacology and therapeutics, prescribing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
(13 reference statements)
0
29
0
Order By: Relevance
“…In terms of CPT topics, most articles (32%) evaluated competencies in antimicrobial prescribing and resistance, and in general prescribing (26%). Most studies (85%) used a cross‐sectional survey as the primary evaluation method; other evaluation methods comprised clinical cases ( n = 3) 10, 21, 22, clinical vignettes ( n = 3) 23, 24, 25, multiple‐choice exams ( n = 2) 10, 26, therapeutic consultations with patients in general practice ( n = 1) 27, drug prescriptions during internship ( n = 1) 28 and a mixture of quantitative and qualitative methods ( n = 1) 29. In total, 10 339 final‐year medical students were involved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of CPT topics, most articles (32%) evaluated competencies in antimicrobial prescribing and resistance, and in general prescribing (26%). Most studies (85%) used a cross‐sectional survey as the primary evaluation method; other evaluation methods comprised clinical cases ( n = 3) 10, 21, 22, clinical vignettes ( n = 3) 23, 24, 25, multiple‐choice exams ( n = 2) 10, 26, therapeutic consultations with patients in general practice ( n = 1) 27, drug prescriptions during internship ( n = 1) 28 and a mixture of quantitative and qualitative methods ( n = 1) 29. In total, 10 339 final‐year medical students were involved.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies examined students' competencies regarding general prescribing 10, 21, 22, 26, 27, 28, 42, 50, 80, 81, 82. Six studies, including a large study of 2413 UK students and graduates, reported that students felt that there was a lack of learning opportunities related to rational prescribing during their medical training, and that they felt underprepared for their prescribing responsibilities 10, 22, 29, 80, 81, 82.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Pharmacology teaching enhances the knowledge and skill of medical students about the different drug formulations and their usefulness in the treatment of various diseases. [5] Even though the art of writing prescriptions is learnt during their second year, the de -learning starts once they enter their third-year clinics, this may be due to increased work load, casual attitude, and no fear of assessment. The reason for this callous attitude needs to be deciphered.…”
Section: Introductionmentioning
confidence: 99%
“…The principal goal of clinical pharmacology and therapeutics is "to improve the care of patients by promoting the safe and effective use of medicines and to evaluate and introduce new therapies" [39]. Therefore, the answer remains in improving clinical pharmacology teaching and learning in undergraduate curriculum [40,41] with necessary assessment program regarding prescribing skill [40] need to incorporate with the hope situation will improve to provide better health care for common people of this planet.…”
mentioning
confidence: 99%